The Good, the Bad and the Agent: An Analysis of Player Representation in Professional Football in the UK - Tetrault, Toby J (2013)
The subject of football agents is shrouded in mystery, with public awareness of the industry limited and only controversy reaching the media; empirical research is needed to provide insight, which is otherwise absent. This paper aims to understand the mechanisms that facilitate transactions for football clubs and whether the principal-agent problem reduces the overall value of a contract, in accordance with transaction cost economics.